Comparative Physiological, Biochemical, and Proteomic Responses of Photooxidation-Prone Rice Mutant 812HS under High Light Conditions - Aisha Almakas (MDPI AG, 2021)
Photosynthetic efficiency decreases as light energy surpasses the photosynthesis capacity. This study was designed to investigate the potential effects of high-intensity light on the photooxidation-prone mutant 812HS of rice and its wild-type 812S during yellow and recovering stages. Results showed that in the yellowing stage, light oxidation occurs due to the exposure of mutant 812HS leaves to the high sunlight, which causes yellowing of the leaves, leading to a reduction in the photochemical activities, physiological mechanisms, and protein contents in mutant 812HS. In the recovery stage, mutant 812HS leaves were exposed to the maximum high brightness, the mutant’s leaves were draped with a dark cover to decrease the exposure of leaves of the plants from direct sunlight, which leads to the restoration of the green color again to the mutant 812HS leaves, leading to improving the performance of the photochemical activities, physiological mechanisms, and protein contents in mutant 812HS. Exposing leaves of mutant 812HS to high light at the yellow stage also resulted in a decrease in the net photosynthetic rate (Pn) in carotenoids content and chlorophyll a and b. Similarly, chlorophyll fluorescence of mutant 812HS decreased in (O-I-J-I-P) curves, and the ATP content, Mg2+-ATPase, and Ca2+-ATPase activities also decreased. An increase in energy dissipation was observed, while ABS/RC, DI0/RC, and TR0/RC values in mutant 812HS at the yellow stage increased. During photooxidation, an increase in O2•– and H2O2 contents was observed in mutant 812HS. While O2•– and H2O2 contents were decreased in mutant 812HS at the recovery stage. The rate of thylakoid membrane protein content was significantly decreased in mutant 812HS at the yellow stage, while at the recovery stage, there was no significant decrease. Our findings showed that photooxidation prompted oxidative damages and lipid peroxidation that caused severe damages to the membranes of the cell, photosynthetic pigments degradation, protein levels, and photosynthesis inhibition in mutant 812HS.